Analysis of the Influence of Product Attributes and Beliefs on Stock Market Product Purchase Decisions with Attitude as a Mediating Variable - Ikka Wijayanti; Moechammad Nasir; Muzakar Isa (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of product attributes and beliefs on purchasing decisions for stock market products, with Attitude as a mediating variable. This is explanatory research using a quantitative approach. The population comprised all individuals/students who have made purchasing decisions, experience, or interest in investing in stocks in the Indonesian capital market, both those who have made stock investment transactions and those who have recently purchased shares. The sampling technique used was non-probability sampling with a purposive sampling approach. The sample size was 275 respondents. The data used was primary. This study employed a quantitative data analysis method using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results indicate that product attributes and beliefs positively and significantly influence consumer attitudes. Consumer attitudes and product attributes positively and significantly influence purchasing decisions. Beliefs have a positive but insignificant influence on buying decisions. Consumer attitudes can mediate the relationship between product attributes and beliefs on buying decisions.